"Brazilian Butt Lift" under Local Anesthesia: A Novel Technique Addressing Safety Concerns. Issue 6 (December 2018) - Chia, Christopher T.; Theodorou, Spero J.; Dayan, Erez; Tabbal, Georges; Del Vecchio, Daniel
Abstract : Background: The gluteal lift ("Brazilian butt lift") has improved significantly in technique and in outcomes. Some postulate that fat embolism occurs because of damage to veins superficial to the gluteus muscles and that fat must be injected intramuscularly to achieve satisfactory aesthetic results. The purpose of this article is to present data where gluteal lift is performed under local anesthesia, address safety concerns, and clarify these speculations. Methods: All patients underwent gluteal lift under local anesthesia using oral medications and tumescent infiltration. Fat was harvested by closed-system liposuction, separated by gravity, injected using a peristaltic pump and reticulating basket cannulas. Results: Thirty-two female patients with an average age of 38.6 years and a body mass index of 24.8 kg/m 2 underwent 47 gluteal lift operations under local anesthesia over 52 months. The average volume of injected fat was 359 ml per buttock. There were no deaths or complications. Conclusions: Recent concerns regarding buttock injections have been raised due to death from fat embolism. Despite numerous theories on the mechanism of entry, the fact that venous injury occurs with the introduction of boluses of fat in enough quantities to cause mechanical disruption of the cardiopulmonary circuit is not in dispute. The authors believe this cannot occur in the awake patient without the surgeon being acutely aware of a misguided cannula. These data suggest that buttock fat grafting under local anesthesia is a safe and effective procedure with an excellent safety profile and durable results. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.